Simultaneous radical cystectomy and nephroureterectomy in the treatment of panurothelial carcinoma: a systematic review and single-arm meta-analysis - Liu, Yang; Zhang, Huimin; Wen, Zhi; Jiang, Yu; Huang, Jing; Wang, Chongjian; Chen, Caixia; Wang, Jiahao; Bao, Erhao; Yang, Xuesong (Frontiers in Oncology, 2023)
Background: Panurothelial carcinoma is a rare and aggressive malignancy that requires effective treatment strategies to enhance patient outcomes.We conducted a systematic search of English publications in databases including PubMed, Embase, Cochrane Library, and Web of Science up to May 2023.The quality of the literature was assessed using the Newcastle-Ottawa Scale (NOS) and the Methodological Quality and Synthesis of Case Series and Case Reports tool. Data statistics and analysis were performed using Stata 15.1 software (StataSE, USA).Results: Six studies involving 339 patients were included in the analysis. Meta-analysis revealed that Simultaneous Radical Cystectomy and Nephroureterectomy had 2-year and 5-year overall survival rates of 68% (95% CI 60%-76%, I 2 = 12.4%, P < 0.001) and 44% (95% CI 36%-53%, I 2 = 0, P < 0.001), respectively. The 2-year and 5-year progression-free survival rates were 91% (95% CI 86%-95%, I 2 = 95%, P < 0.001) and 65% (95% CI 58%-73%, I 2 = 91.5%, P < 0.001), respectively. The 2-year and 5-year cancer-specific survival rates were 73% (95% CI 66%-81%, I 2 = 16.7%, P < 0.001) and 57% (95% CI 49%-66%, I 2 = 0, P < 0.001), respectively. Additionally, the incidence of minor complications was 19% (95% CI 15%-23%, P < 0.01), major complications was 49% (95% CI 34%-63%, P < 0.01), and the intraoperative blood transfusion rate was 53% (95% CI 44%-61%, P < 0.01).Conclusions: Simultaneous radical cystectomy and nephroureterectomy represent feasible approaches for the treatment of Panurothelial carcinoma. Nonetheless, a comprehensive assessment of the surgical risks and benefits is imperative, and larger-scale prospective cohort studies are required to validate therapeutic efficacy.